The Importance of the Strategic Location of the Municipality of Qobba: A Political Geography Study - Al-Ghaithi, Masoud Mohammed (Journal of Tikrit University for Humanities, 2025)
This study aims to show the importance of the strategic location of the municipality of Al-Qubba, given the study area’s lack of scientific studies that show the significance of its location and resources that give it great importance. Through examining its components, it will be found that it lacks sufficient human power compared to the municipalities that border it in its territory represented by Al-Jabal Al-Akhdar. Its geographical location makes it of pivotal importance that can be exploited from an economic, tourism and military perspective. In this study, the Geographic Information Systems program (GIS) was used, in addition to the Digital Elevation Model, known scientifically by the abbreviation (DEM), and the researcher also used the statistical analysis program (Statistical Package for the Social Sciences) to perform some calculations and statistics.